Early Spontaneous Movements of Infants With Hypoxic-Ischemic Encephalopathy. Issue 1 (January 2021) - Alkan, Halil; Kahraman, Aysu; Mutlu, Akmer
Abstract : Objective: The aim of this study was to determine motor repertoire at 3 to 5 months of age in infants with hypoxic-ischemic encephalopathy (HIE) and to examine changes according to HIE severity. Methods: Participants were 38 infants aged 3 to 5 months with HIE and 38 infants in the comparison group. The general movement assessment and the Motor Optimality Score (MOS) were used. Results: Infants in the HIE group had a significantly lower total MOS and scores for fidgety movements, age adequacy of motor repertoire, and quality of movement patterns compared with the comparison group. Infants with grade III HIE compared with grade I had a significantly lower MOS. Conclusions: Infants with HIE had poorer motor repertoire at age 3 to 5 months when compared with peers. Motor repertoire deteriorated as HIE severity increased. Detecting potential developmental delays as early as possible allows for early intervention and rehabilitation in this population. Abstract : The aim of this study was to determine motor repertoire at 3 to 5 months of age in infants with hypoxic-ischemic encephalopathy and to examine how this repertoire changes according to severity.